2018
DOI: 10.1093/jscr/rjy156
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic approach for a presacral myelolipoma resembling a liposarcoma

Abstract: Myelolipomas are rare benign tumors that are commonly found in the adrenal glands. Extra-adrenal locations are rare, and presacral myelolipomas represent the most common extra-adrenal location. The differential diagnosis of malignant presacral neoplasms is very challenging. We present a case of a presacral neoplasm that was completely removed with a laparoscopic approach and diagnosed as a myelolipoma only after pathological examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The right side was dominated by adipose tissue, and only a little bone marrow hematopoietic tissue was scattered among adipocytes ( Figures 2C, D ). Myelolipoma is more common in the adrenal gland than in the thoracic cavity, retroperitoneum, presacral area ( 4 ), mediastinum, spleen, lung, testis, soft tissue, and other parts. It has been reported that ( 5 ) occurs simultaneously in the adrenal gland and the contralateral pelvic cavity, and it is extremely rare that the primary tumor occurs in the liver ( 6 , 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The right side was dominated by adipose tissue, and only a little bone marrow hematopoietic tissue was scattered among adipocytes ( Figures 2C, D ). Myelolipoma is more common in the adrenal gland than in the thoracic cavity, retroperitoneum, presacral area ( 4 ), mediastinum, spleen, lung, testis, soft tissue, and other parts. It has been reported that ( 5 ) occurs simultaneously in the adrenal gland and the contralateral pelvic cavity, and it is extremely rare that the primary tumor occurs in the liver ( 6 , 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there have been several case reports of extra-adrenal myelolipoma in which a definitive preoperative diagnosis could not be made. 2 …”
Section: Discussionmentioning
confidence: 99%
“…However, Shen C et al argued that symptomatic patients with a tumor size lager than 7 cm should be candidates of surgery, and asymptomatic patients with smaller tumors should be followed up closely [26] . In intraosseous and presacral EAMs, surgery is indicated, especially for patients with clinical symptoms, and the masses greater than 7 cm [12] , [28] , [29] . It is generally suggested that surgical intervention may be necessary if the mass is larger than 4 cm in diameter [3] , [21] .…”
Section: Discussionmentioning
confidence: 99%